A new species of Ferula (Apiaceae) from Malta - Brullo, Salvatore; Brullo, Cristian; Cambria, Salvatore; Giusso Del Galdo, Gianpietro; Salmeri, Cristina; Bacchetta, Gianluigi (Phytotaxa, 2018)
Ferula melitensis, a new species from the Malta Archipelago, is described and illustrated. It belongs to the taxonomic group of F. communis, showing close relationships mainly with F. tunetana, F. arrigonii, F. communis s.str. and F. glauca, from which it differs in several features regarding the stem, leaves (mainly for shape and size of terminal segments), flowers and mericarps; other significant differences regard the ecology and phenology. The investigations, carried out on living plants, herbarium material and literature data, regard the morphological analysis of vegetative and reproductive structures, the anatomy of terminal leaf segments and mericarps, as well as the shape and size of seedlings. Previous phylogenetic approaches, based on nuclear and plastidial genome, have allowed to clarify better the relationships among F. melitensis and the other species of this group.